Promoting knowledge cities agenda through institutionalization of spatial planning and decision support system in Malaysia - Abdullah, Muhammad Faris; Abdullah, Alias; Ibrahim, Mansor; Boerboom, Luc; Geneletti, Davide (2007)
The introduction of innovative systems like Spatial Planning and Decision Support System (SPDSS) can only be effective and efficient if they are integrated as part of the existing structures and working processes within the organisation. SPDSS is an approach that uses an interactive computer-based system designed to support users like town planners, government officials, councillors and mayors in achieving a higher effectiveness of decision making in planning while solving a semi-structured spatial decision problem.